The magic kingdom - Banks, Russell, 1940- (Alfred A. Knopf, 2022)
"In 1971, a property speculator named Harley Mann begins recording his life story onto a reel-to-reel machine. Reflecting on his childhood in the early 20th century, Harley recounts that after his father's sudden death, his family migrated down to Florida-mere miles away from what would become Disney World-to join a community of Shakers. Led by Elder John, a generous man with a mysterious past, the colony devoted itself to labor, faith, and charity, rejecting all temptations that lay beyond the property. Though this initially saved Harley and his family from complete ruin, when Harley began falling in love with Sadie Pratt, a consumptive patient who lived on the grounds, his loyalty to the Shakers and their conservative worldview grew strained and, ultimately, broke. As Harley dictates his story across more than half-a-century, the truth about Sadie, Elder John, and the Shakers comes to light, clarifying the past into a world we recognize today"--